Encoding-Stage Adaptation Effects: Long-Term Memory. (February 2018) - Peacock, Candace E.; Gözenman, Filiz
Given adaptation changes perceptual experience, it probably shapes long-term memory (LTM). Across four experiments, participants were adapted to strongly gendered (male, female: Experiments 1 and 2) or aged faces (old, young: Experiments 3 and 4) before LTM encoding and later completed an LTM test in which the encoded faces were morphed with the opposite end of the relevant continuum. At retrieval, participants judged whether probe faces were more or less male or female or young or old than when presented during encoding. For male, female, and young faces, encoding-stage adaptation significantly shifted the point of subjective equality in the unadapted direction. Additionally, encoding-stage adaptation significantly enhanced recognition of faces during LTM retrieval. We conclude that encoding-related adaptation is reflected in LTM.